Asymmetric information and bank runs - Chao Gu (Cornell University, Center for Analytical Economics (CAE), 2007)
It is known that sunspots can trigger panic-based bank runs and that the optimal banking contract can tolerate panic-based runs. The existing literature assumes that these sunspots are based on a publicly observed extrinsic randomizing device. In this paper, I extend the analysis of panic-based runs to include an asymmetric-information, extrinsic randomizing device. Depositors observe different, but correlated, signals on the stability of the bank. I find that if the signals that depositors obtain are highly correlated, there exists a correlated equilibrium for some demand deposit contracts. In this equilibrium, either a full bank run, or a partial bank run, or non bank run occurs depending on the realization of the signals. Computed examples indicate that in some economies, a demand-deposit contract that tolerates bank runs and partial bank runs is optimal; while in some other economies a run-proof contract is optimal.
Keywords: D82; G21; P11; 330; bank runs; randomizing device; sunspot equilibrium; correlated equilibrium; imperfect information; Bankenkrise; Asymmetrische Information; Spieltheorie; Theorie